Second-Class Citizen in the Heliophysics Community - Kahler, Stephen (Frontiers in Astronomy and Space Sciences, 2022)
The study of solar energetic particles (SEPs) is an important area of solar research and space weather. An SEP event extends over large regions of the heliosphere, involves energy ranges varying by decades, and evolves over various time and spatial scales and with ion composition, but with SEP observations limited to in situ detections on a few spacecraft for any given event, we are unable to observe these properties synoptically. Solar studies in general are the beneficiaries of imaging and remote sensing observations over practically all wavelengths and timescales from ground and space based detectors that drive increasingly highly sophisticated models. I see this divide as creating a two-class system for researchers, with us SEP researchers as second class members. Following a brief review of my experience with solar imagery and failed ideas on remote imaging of SEP events, I review two remarkable developments that give hope for some new SEP imaging technique. Finally, I discuss two poorly understood questions of impulsive and gradual SEP events that I think can be feasibly approached with current modeling techniques.